ELEMENTAL GEOCHEMISTRY AND TECTONIC SIGNIFICANCE OF CAMBRIAN BASALTS FROM THE NORTHERN SIDE OF THE NALATI MOUNTAIN - Qian Q.; Long L.L.; Gao J.; Xu S.L.; He G.Q.; Klemd R.; Xiong X.M. (My University, 2007)
This paper reports the major and trace elemental compositions of Cambrian (516.3 +/- 7.4Ma) tholeiitic basalts from the northern side of the North Nalati fault (NNF) in the Chinese southwestern Tianshan Mountains. The basalts are typical transitional (T-) type mid-ocean ridge basalts (MORB), characterized with low Al2O3 (12.71% similar to 14. 14%) and P2O5 (0. 09% similar to 0. 21%), moderate TiO2(1.39% similar to 2.35%) and MgO (5.35% similar to 8. 14%) and high total Fe (11.74% similar to 16.03% as Fe2O3) contents, as well as flat chondrite-normalized rare earth element (REE) patterns. (La/Sm) r, and (Y/Nb) (N) ratios are close to unit, also substantiating a T-MORB affinity. Crustal contamination and subduction fluid activity are not evidenced by the low Th/Ta ratios (0. 8 similar to 1. 5) and lack of depletion of high field strength elements (Nb, Ta, Zr, Hf and P). Some T-MORB samples have relatively enriched iron and titanium and lower Mg # (0. 40 similar to 0. 49) and Cr (53 x 10 (-6) similar to 110 x 10 -6) values, and can be classified as Fe-Ti basalts (ferrobasalts), which are defined as having FeOT > 12%, TiO2 > 2% and FeOT/MgO > 1. 75. The Fe-Ti basalts were most likely produced from the MORB-type magma through relatively high degree of Fenner trend differentiation at a propagating spreading centre of mid-ocean ridge. The T-MORB and Fe-Ti basalts are believed to be counterparts of the Terskey ophiolite belt along the southern margin of Kyrgyzstan Northern Tianshan, and consequently fragments of the Terskey ophiolites. We propose that (1) the Terskey ocean developed in the Chinese southwestern Tianshan region in Cambrian; (2) the NNF is the eastern extension of the Nikolaev Line, and represents an early Paleozoic suture zone formed by closure of the Terskey ocean.
Keywords: CAMBRIAN; FE-TI BASALT; NIKOLAEV LINE; NORTH NALATI FAULT; SOUTHWESTERN TIANSHAN; TERSKEY OCEAN; Paleozoic::Cambrian; Палеозой::Кембрийская